2007
DOI: 10.1007/s10620-006-9563-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Naloxone-3-Glucuronide and N-Methylnaloxone on the Motility of the Isolated Rat Colon After Morphine

Abstract: The effect of the opioid antagonists naloxone-3-glucuronide and N-methylnaloxone on rat colon motility after morphine stimulation was measured. The rat model consisted of the isolated, vascularly perfused colon. The antagonists (10(-4) M, intraluminally) and morphine (10(-4) M, intra-arterially) were administered from 20 to 30 and from 10 to 50 min, respectively. Colon motility was determined by the luminal outflow. The antagonist concentrations in the luminal and venous outflow were measured by high-performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…This suggests that the action of opioids in the GI tract is mediated mainly by peripheral receptors. Highly polar naloxone derivatives peripherally antagonize the effect of morphine-delayed GI motility in the perfused isolated rat colon [93]. However, some studies imply that only the CNS is involved.…”
Section: Opioid Receptor Ligandsmentioning
confidence: 99%
“…This suggests that the action of opioids in the GI tract is mediated mainly by peripheral receptors. Highly polar naloxone derivatives peripherally antagonize the effect of morphine-delayed GI motility in the perfused isolated rat colon [93]. However, some studies imply that only the CNS is involved.…”
Section: Opioid Receptor Ligandsmentioning
confidence: 99%
“…However, optimal collision energy was not applied to NLL and NLG to minimize some interference peaks near the analyte peaks of interest. The instrument parameters for monitoring NLX, NLL, NLG, NLX-d 5 , NLL-d 5 , and NLG-d 5 during method validation and sample analysis were as follows: TIS temperature, 600 • C; TIS voltage, 3500 V; curtain gas (CUR), nitrogen, 25; nebulizing gas (GS1), 80; TIS gas (GS2), 60; collision gas, 10; declustering potential (DP), 80 V; entrance potential (EP), 10 V; collision energy (CE), 52 eV for NLX, NLG, NLXd 5 , and NLG-d 5 …”
Section: Mass Spectrometric Conditionsmentioning
confidence: 99%
“…The potency of NLL to precipitate opioid withdrawal from acute morphine dependence has been reported [4]. It has also been demonstrated that NLG can antagonize the mobility-lowering effect of morphine in the rat colon [5,6]. Therefore, development of a bioanalytical method for the quantification of NLX, NLL, and NLG in plasma samples is needed to better understand their toxicokinetic and pharmacokinetic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The N-dealkylation and reduction of 6-oxo group further precede glucuronidation and naloxone-3-b-D-glucuronide is the predominant metabolite of naloxone in humans [16]. Naloxone-3-b-D-glucuronide has demonstrated peripheral opioid antagonist activity in an ex-vivo model and in humans [20,21]. Therefore, its pharmacokinetics profile was evaluated in this study.…”
Section: Introductionmentioning
confidence: 99%